Hubungan Kondisi Rumah dengan Penularan TB Paru di Puskesmas Ch. M. Tiahahu Kecamatan Sirimau Kota Ambon - Youndry Tahalele; Gracia Victoria Souisa; Samuel Titaley (MOLUCCAS HEALTH JOURNAL, 2019)
Tuberculosis is a contagious disease caused by TB (Mycobacterium tuberculosis). Houses that do not meet health requirements are a risk factor for transmission of pulmonary tuberculosis. The purpose of this study was to determine the relationship of home conditions with transmission of pulmonary tuberculosis in Puskesmas Ch. M. Tiahahu Sirimau Sub-district, Ambon City, 2017. The research method used is analytical method with Cross Sectional approach. Sampling using Total Sampling with total sample that is 37 sample. Data collection using questionnaires and measurement sheets. Data analysis includes univariate and bivariate analysis using computer statistic program. The result of bivariate analysis showed no correlation relationship with transmission of pulmonary tuberculosis (p = 0,093), there was relation of humidity with transmission of pulmonary tuberculosis (p = 0,036), no ventilation relationship with pulmonary tuberculosis transmission (p = 0,742), transmission of pulmonary tuberculosis (p = 0,022) .The conclusion of this research is the relation of humidity and density and there is no correlation of lighting and ventilation with transmission of pulmonary tuberculosis in Puskesmas Ch. M. Tiahahu Sirimau Sub-district, Ambon City 2017. For Pulmonary TB patient, have a good knowledge about pulmonary TB disease, by always hearing counseling or socialization from health center or other health service, to know about TB disease Always support from family in the form of motivation or spirit given from father or mother and child Pulmonary TB patients can seek treatment regularly and recover quickly For Puskesmas a gar always provide guidance and information or socialization to Pulmonary TB sufferers about the requirements of healthy house so as to prevent transmission of pulmonary TB disease.